2009
DOI: 10.1021/ac9019494
|View full text |Cite
|
Sign up to set email alerts
|

Extractive Electrospray Ionization Mass Spectrometry for Sensitive Detection of Uranyl Species in Natural Water Samples

Abstract: Ambient mass spectrometry has been increasingly applied for sensitive detection of trace organic compounds present in complex matrixes. In the real world, detection of trace amounts of inorganic species, particularly with speciation information, is of great significances. Herein a method based on extractive electrospray ionization (EESI) tandem mass spectrometry (MS/MS) has been established for rapid detection of radioactive inorganic species in natural water samples. Negatively charged uranyl acetate undergoe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 68 publications
1
52
1
Order By: Relevance
“…More , had previously been prepared in a Bbottom-up^approach by insertion of U + into NO in an ion-molecule reaction [28], our experiments demonstrated that the species can also be created in a CID reaction. Formation of the nitrido species by transfer of N from cyanide was confirmed using precursors labeled with -in a 3-D quadrupole ion trap has been reported [26,30], and the structure of the species has been determined using infrared multiple-photon photodissociation (IRMPD) spectroscopy [31]. However, the experiments reported here demonstrate that the chemistry of product ions from both systems can be explored more accurately in the 2-D LIT.…”
Section: +mentioning
confidence: 80%
“…More , had previously been prepared in a Bbottom-up^approach by insertion of U + into NO in an ion-molecule reaction [28], our experiments demonstrated that the species can also be created in a CID reaction. Formation of the nitrido species by transfer of N from cyanide was confirmed using precursors labeled with -in a 3-D quadrupole ion trap has been reported [26,30], and the structure of the species has been determined using infrared multiple-photon photodissociation (IRMPD) spectroscopy [31]. However, the experiments reported here demonstrate that the chemistry of product ions from both systems can be explored more accurately in the 2-D LIT.…”
Section: +mentioning
confidence: 80%
“…All the experiments were carried out using a linear trap quadruple mass spectrometer (LTQ-XL, Thermo Fisher Scientific, San Jose, CA) installed with a homemade EESI source, which was previously described in detail [26,[32][33][34][35]. The schematic illustration of EESI-MS is shown in Fig.…”
Section: Instrumentationmentioning
confidence: 99%
“…As reported in 2006, extractive electrospray ionization mass spectrometry (EESI-MS) was able to detect TNT in waste water, and trace atrazine in undiluted urine [26], showing promising applications in environmental studies. To date, EESI-MS has been applied to direct analysis of various samples, including exhaled human breath [27,28], skin [29], food [29][30][31], natural water [32], toothpaste [33], native proteins [34], etc. In this study, low ppb levels of TBBPA derivatives in waste water were detected for the first time with EESI-MS/MS.…”
Section: Introductionmentioning
confidence: 99%
“…Most of EESI-MS studies have been carried out for the analysis of organic compounds, although the successful detection of uranium and its salts using EESI-MS has been reported [55]. In this study, EESI-MS was used for the fast and sensitive detection of trace levels of lead in aqueous liquid samples.…”
Section: Introductionmentioning
confidence: 99%